KARAKTERISASI BAKTERI PENGHASIL a-AMILASE DAN IDENTIFIKASI ISOLAT C2 YANG DIISOLASI DARI TERASI CURAH SAMARINDA, KALMANTAN TIMUR [Characterization bacteria Producing a- amylase and Identification of Strains C2 Isolated from bulk shrimp-paste in Samarinda, East Kalimantan] - Soeka, Yati Sodaryati (BERITA BIOLOGI, 2016)
Enzymes a-amylase is one of the enzymes used in process of starch degradation. This present study was aimed to characterize and identify of a-amylase producing strain isolated from bulk shrimp-paste in Samarinda, East Kalimantan was carried out. An experiment was conducted to examine influences of incubation, carbon source, substrate concentration temperature for incubation, pH of media, and addition of metal ions. Identification of strain C2 was carried out by using Wizard Genomic DNA Purification Kit (Promega). The result showed that optimum activity of a-amylase from C2 after six days incubation was 18.93 U/mL. Tests on the type of substrate , soluble starch was the best source to produce a- amylase (14.51 U/mL). However, at concentration of 2 % and incubation temperature at 40Â°C, enzymatic activity was decreased to 12.56 U/mL and 12.79 U/mL, respectively within residual activity of 74.75%. The enzyme activity was 16.43 U/mL and its residual activity was 39.14 % when it was assayed at pH 8.5. Addition of metal ions in the form of divalent and monovalent cations (1 mM) showed that the enzyme could be activated by ion Ca2+ while ion Cu2+, Co2+, Mg2+, Zn2+ , Na+ Â decrease the activity of the enzyme. Identification of strain C2 using molecular characterization demonstrated that partial sequences of 16S rDNA reffered to as Bacillus subtilis.